Regulating Coastal Zones International Perspectives on Land Management Instruments - Alterman, Rachelle; Pellach, Cygal (Urban Planning and Environment, 2021)
Regulating Coastal Zones addresses the knowledge gap concerning the legal and regulatory challenges of managing land in coastal zones across a broad range of political and socio-economic contexts. In recent years, coastal zone management has gained increasing attention from environmentalists, land use planners, and decision-makers across a broad spectrum of fields. Development pressures along coasts such as high-end tourism projects, luxury housing, ports, energy generation, military outposts, heavy industry, and large-scale enterprise compete with landscape preservation and threaten local history and culture. Leading experts present fifteen case studies among advanced-economy countries, selected to represent three groups of legal contexts: signatories to the 2008 Mediterranean ICZM Protocol, parties to the 2002 EU Recommendation on Integrated Coastal Zone Management, and the USA and Australia. This book is the first to address the legal-regulatory aspects of coastal land management from a systematic cross-national comparative perspective. By including both successful and less-effective strategies, it aims to inform professionals, graduate students, policy makers, and NGOs of the legal and socio-political challenges as well as the better practices from which others could learn.